2010
DOI: 10.1007/s00213-010-1892-x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental consequences of perinatal cannabis exposure: behavioral and neuroendocrine effects in adult rodents

Abstract: RationaleCannabis is the most commonly used illicit drug among pregnant women. Since the endocannabinoid system plays a crucial role in brain development, maternal exposure to cannabis derivatives might result in long-lasting neurobehavioral abnormalities in the exposed offspring. It is difficult to detect these effects, and their underlying neurobiological mechanisms, in clinical cohorts, because of their intrinsic methodological and interpretative issues.ObjectivesThe present paper reviews relevant rodent st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
86
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(94 citation statements)
references
References 109 publications
(173 reference statements)
8
86
0
Order By: Relevance
“…Moreover, it has been suggested that exogenous cannabinoids during adolescent maturation may result in long-term effects on HPA function which might affect subsequent stress reactivity, cognitive functioning, and emotionally relevant behavior (Viveros et al 2005;Realini et al 2009Realini et al , 2011Rubino et al 2009;Buwalda et al 2011;Campolongo et al 2011;LlorenteBerzal et al 2011). Hence, the reversal effects observed during the late-adolescent period, but not during adolescence, could be the result of a developing CNS that is more sensitive to environmental influences, such as stress and drugs, than the adult CNS.…”
Section: Alterations In Cb1r and Grs In The Stress Circuitmentioning
confidence: 99%
“…Moreover, it has been suggested that exogenous cannabinoids during adolescent maturation may result in long-term effects on HPA function which might affect subsequent stress reactivity, cognitive functioning, and emotionally relevant behavior (Viveros et al 2005;Realini et al 2009Realini et al , 2011Rubino et al 2009;Buwalda et al 2011;Campolongo et al 2011;LlorenteBerzal et al 2011). Hence, the reversal effects observed during the late-adolescent period, but not during adolescence, could be the result of a developing CNS that is more sensitive to environmental influences, such as stress and drugs, than the adult CNS.…”
Section: Alterations In Cb1r and Grs In The Stress Circuitmentioning
confidence: 99%
“…alcohol, nicotine, morphine or cannabis) may pose severe threats -unrelated to miscarriage or placental deficits -to the foetus, providing the foundation of neurobehavioral teratology (12). CNS vulnerability is a leading fingerprint of harmful developmental drug effects, and predominantly manifest as functional impairments in early childhood or adolescence, much less so by birth (13).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from neuron subtype-specific deletions suggests that CB1R may have different functions and pharmacological properties in different cell types (reviewed in [17]) and that its subcellular localization may mediate distinct signaling [18,19]. Endocannabinoids play critical roles during fetal brain development, being involved in neuronal differentiation, survival and the regulation of neurotransmitter systems [20,21,22]. …”
Section: Introductionmentioning
confidence: 99%